Total energy expenditure and body composition in early infancy. Issue 5 (November 1996) - Wells, J C; Cole, T J; Davies, P S
Abstract : In adults greater energy expenditure, primarily on physical activity, is associated with greater leanness. Such an association has proved more difficult to demonstrate in infants, partly due to the difficulty of measuring fatness and free living energy expenditure in this age group. Stable isotope techniques now make such investigations more viable. OBJECTIVE: The relationship between body composition and energy expenditure was investigated in 12 week infants. METHODS: Total energy expenditure and fat mass were estimated using the doubly labelled water technique. SUBJECTS: 92 normal healthy infants. RESULTS: Fat mass was correlated with both triceps and subscapular skinfold thicknesses (p < 0.001). After controlling for body size, age was a significant predictor of fat mass (p = 0.003), whereas total energy expenditure was not (p = 0.463). CONCLUSIONS: The cross sectional link between activity level and fatness in young infants, reported previously, does not persist when energy expenditure is considered.